Case Report: Activated PI3-kinase-δ syndrome and ovarian malignancies: a case series from the European ESID-APDS registry - Esposto, Maria Pia; Mahlaoui, Nizar; Abolhassani, Hassan; Van Aerde, Koen; Cesaro, Simone; Chandra, Anita; Ehl, Stephan; Kracker, Sven; Suarez, Felipe; Barlogis, Vincent; Parisi, Alice; Maccari, Maria Elena; et al. (Frontiers in Immunology, 2025)
Activated phosphoinositide-3-kinase-delta (PI3Kδ) syndrome (APDS) is an autosomal dominant inborn error of immunity (IEI) characterized by combined immunodeficiency and immune dysregulation with increased risk for lymphoma and other non-lymphoid malignancies. We describe five patients with ovarian malignancies among 110 female APDS patients participating in the European Society for Immunodeficiencies (ESID) registry and identified three additional cases in the literature. These findings document a relevant predisposition to these non-hematological malignancies in APDS patients.